The Effect of Empowerment and Assistance on MSME Performance and Digital-based Business Sustainability in Makassar City - Saharuddin, Saharuddin (Journal of Entrepreneur, Business and Management, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the global economy as a major contributor to economic growth and job creation. However, MSMEs often face challenges in improving operational performance and facing rapid changes in the business environment, especially in today's digital era. The quantitative research approach was used using a questionnaire distributed to owners and business actors in the Makassar City area. The population in this study is all business actors in the city of Makassar, both those who have participated in empowerment and mentoring programs and those who have never participated in these programs. The sample in this study is 70 business actors who were selected by purposive sampling. This study aims to investigate the influence of empowerment and mentoring on the performance of Micro, Small, and Medium Enterprises (MSMEs) and the sustainability of digital-based businesses in Makassar City, so the analysis tool used is multiple linear regression analysis. Furthermore, to find out and prove the influence of the significance of each independent variable on the dependent variable partially, the t-test is used, while to find out the influence of the significance of the independent variable on the dependent variable simultaneously, the F-test is used. The results of the analysis show that the empowerment and mentoring of MSMEs has a significant positive impact on the performance of MSMEs. In addition, the performance of MSMEs has also proven to have a strong influence on the sustainability of digital-based businesses. Mediation analysis shows that the empowerment and assistance of MSMEs not only directly affects the performance of MSMEs, but also has an impact on the sustainability of digital-based businesses through MSME performance mediation. These findings have important implications for practitioners and policies in designing effective empowerment and mentoring strategies to improve the performance and sustainability of MSME businesses in the ever-changing digital era.Keywords: MSMEs, empowerment, mentoring, performance, business sustainability, digital era